Literature Review: Exploration of Bioactive Components of Avicennia marina and Its Biological Activities - Budastra, Cintya; Ulya, Tuhfatul; Maulidya, Selvira Anandia Intan; Purnomo, Indra; Lisnasari, Baiq Risky Wahyu; Permatasari, Lina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indonesia, as a maritime nation, possesses numerous mangrove ecosystems that have significant potential for exploring their benefits. One species of mangrove that has attracted attention is Avicennia marina, which contains various bioactive compounds. This article aims to provide a comprehensive review of the bioactive components of the Avicennia marina plant and its biological activities, particularly its therapeutic potential and benefits in the pharmaceutical field. We conducted a literature search to find relevant articles in the PubMed, Scopus, and Google Scholar databases using the keywords: plant identification + Avicennia marina; compound identification + Avicennia marina; biological activity + Avicennia marina. The bioactive content from the leaves, fruits, stems, and roots of Avicennia marina has been shown to exhibit antioxidant, antimicrobial, anticancer, and anti-inflammatory effects. This effect is strongly correlated to the presence of active metabolites of triterpenes, terpene alcohols, diterpenes, tannins, dodecanoic acid, octadecanoic acid, phenolic compound, flavonoid, squalene, and phytol. This indicates that Avicennia marina is a promising natural source for further research in the development of a new drug. Our finding further the notion of Avicennia marina as a potential medicinal plant.